Tailoring the magnetic landscape in Al-doped LaMnO3: an experimental and computational perspective. (1st February 2023) - Bhowmik, Tushar Kanti; Halder, Saswata; Sinha, Tripurari Prasad
Abstract: We have reported the synthesis, structural and magnetic properties of LaAl x Mn1− x O3 (x = 0.05, 0.15, 0.25) in this article. We have synthesized these compounds through the Sol-gel citrate method and performed the Rietveld refinement of X-ray diffraction data to determine the lattice parameters. The surface elemental composition and oxidation states of LaAl0.25 Mn0.75 O3 are investigated using X-ray photoelectron spectroscopy (XPS) in a wide energy window of 0–1200 eV. The magnetic study shows the ferromagnetic transition of these materials. To understand the nature of magnetization from the experiments, we have studied the first principle density functional theory (DFT) and Monte-Carlo simulation. From the DFT calculations, we have confirmed the ferromagnetic structure in the ground state and studied the electronic structure of these materials. The Monte Carlo simulation has been done through the anisotropic Ising model to analyze the origin of magnetic phase transition. We have determined the anisotropy and the interaction constants from the DFT calculations. The double exchange interaction is mainly responsible for the ferromagnetic ground state.